Pengaruh Self-esteem terhadap Fear of Missing Out pada Emerging Adulthood Pengguna Instagram - Amanda Amalia; Indri Utami Sumaryanti (Bandung Conference Series: Psychology Science, 2022)
Abstract. a lot of people consider internet as needs because it allow us to access any information in every situation and one of them via social media. Instagram is a social media platform that have a lot of users, with Instagram we can connect with other people without even facing each other real time. Although, it could cause a lot of problem and one of them is FoMO phenomenon. The most people who experience fomo is emerging adulthood, people with FoMO feel anxious and afraid of missing out on precious moments that others experience in their absence, which leads individuals to check their devices more frequently to stay up-to-date on other people's activities. One that indicates fomo is self-esteem, the purpose of this study was to find out the effect of self-esteem on FoMO on emerging adulthood instagram users in Bandung. The method used is a quantitative study using a simple linear regression analysis technique with 196 sampling of emerging adulthood. The instruments used to collect data are the Fear of Missing Out Scale (Przybylski et al., 2013) which has been adapted by Azmi (2019) and the Rosenberg Self-esteem scale (Rosenberg, 1965) which has been adapted by Maroqi (2018). The results of the study found that self-esteem has a significant effect on FoMO with a negative direction of influence and. the contribution of self-esteem to the FoMO variable is 6.8%. Abstrak. Banyak orang menganggap internet sebagai kebutuhan karena memungkin kita untuk mengakses informasi kapanpun dan dimanapun, dengan internet kita dapat mengakses informasi kapanpun dan di manapun salah satunya melalui sosial media. Instagram merupakan media sosial yang memiliki pengguna paling banyak, dengan instagram kita dapat terhubung dengan orang lain tanpa bertatap muka, namun hal itu dapat menimbulakan masalah salah satunya terjadinya fenomena FoMO. Emerging adulthood merupakan usia yang paling tinggi mengalami FoMO, individu yang mengalami FoMO merasa cemas dan takut tertinggal momen berharga yang dialami orang lain ketika dirinya tidak ada, yang membuat individu menjadi lebih sering mengecek gawai untuk tetap up to date terhadap kegiatan orang lain. salah satu faktor yang dapat mendorong munculnya FoMO adalah self-esteem. Penelitian ini bertujuan untuk mengatahui pengaruh self-esteem terhadap FoMO pada emerging adulthood pengguna instagram di kota Bandung. Metode yang digunakan adalah penelitian kuantitatif dengan menggunakan teknik analisis regresi linear sederhana dengan sampling 196 emerging adulthood. Instrumen yang digunakan untuk pengambilan data adalah Fear of missing out Scale (Przybylski et al., 2013) yang telah diadaptasi oleh Azmi (2019) dan Rosenberg Self-esteem scale (Rosenberg, 1965) yang telah diadaptasi oleh Maroqi (2018). Hasil penelitian menemukan bahwa self-esteem secara signifikan memiliki pengaruh terhadap FoMO dengan arah pengaruh negative. Kontribusi variabel self-esteem terhadap variabel FoMO sebesar 6.8%.